A study on the cannibalism behaviour and predation of the larvae of fall armyworm (Spodoptera frugiperda). Issue 5 (10th May 2022) - Mbuji, Amosi Leonard; Gong, Xueyan; Li, Fen; Yang, Lei; Shi, Xueyan; Peng, Zhengqiang; Zhang, Ying; Wu, Shaoying
Abstract: Cannibalism behaviour in the Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is among of liming factor for mass production of the larvae for laboratory experiment. To understand the change of cannibalism, larvae of 1st, 2nd, and 3rd were used to study cannibalism they were put on the 3rd, 4th, and 5th larvae growth stages in a density of 30, 40, 50, 60, and 70. In this study, the results showed that the functional response of the 3rd ‐5th instar larvae to the 2nd larvae and the 4th–5th instar larvae to the 3rd larvae and 5th and 6th instar larvae to the 4th larvae fitted well with the Holling II mode. The maximum predation of the 3rd‐5th instar larvae on the 2nd instar larvae were 27.17, 74.63, and 232.6 respectively, the maximum predation of the 4th–5th instar larvae on the 3rd instar larvae were 76.92 and 11.82 respectively, and the maximum predation of the 5th–6th instar larvae on the 4th instar larvae were 15.83 and 10.40. The predation of the older larvae to the younger larvae increased with the increase of the density of the younger larvae. This research aims at selecting the minimum number of larvae that will be effective and sustainable for laboratory experiments and minimizing the development of cannibalism in S. frugiperda, reduces crowding for larvae management and promoting healthy larvae. This study provides a pavement of managing larvae ensuring massive indoor larvae rearing to reduce the challenge of inadequate larva for the experiment.